The morning show murders [large type] : a novel - Roker, Al, 1954- (Thorndike Press large print mystery, 2010)
Celebrity chef Billy Blessing struggles to clear his name by solving the murder of his producer, who has been poisoned while eating a dish from Billy's four-star restaurant.